The FEATURES OF ORGANIZING STEAM EDUCATIONAL PROJECTS USING IMMERSIVE TECHNOLOGIES - SOROKO, Nataliia (Physical and Mathematical Education, 2024)
Formulation of the problem. The rapid development of technologies in the modern world opens up new horizons for education. Integrating science, technology, engineering, arts, and mathematics (STEAM) holds particular significance as a transformative approach, fostering interdisciplinary learning and preparing students for the challenges of a knowledge-based and digitized society. The transition from a traditional approach to STEAM education becomes even more captivating with the incorporation of immersive technologies. This direction, merging technical and creative aspects, requires an innovative approach to the organization of educational projects, considering the new opportunities and challenges presented by virtual reality (VR), augmented reality (AR), and mixed reality (MR).Materials and methods. To achieve the goal of our research, we used the following methods: systematic and comparative analysis of pedagogical, psychological, philosophical, and sociological works, methodic literature, and analysis of the pedagogical experience of using immersive technologies to organize STEAM projects at school; synthesis and generalization to formulate the main provisions of the study; interviews and questionnaires of teachers regarding their understanding and attitude to immersive technologies as a means of implementing STEAM projects at school; interpretation of research results. We analyzed 18 scientific sources, including 14 Scopus-indexed articles, two reports (the educational report from Horizon 2020 and the "State of the Industry Report" from the XR Association), and two scientific studies by Ukrainian researchers. Eighty-seven teachers participated in interviews and surveys conducted through Google Forms.Results. Creating and organizing a STEAM educational project using immersive technologies involves the following teacher actions: forming a project name by the student's learning goals, educational content, and the project result as its product; creating a reference project; determining the subject, topic, age of students, project preparation time, learning time, essential immersive technologies; forming the purpose of the first lesson and project tasks to immerse and motivate students about the project; identifying problematic issues that should reflect the actual context or problem. We have characterized teachers' attitudes towards immersive technologies when organizing and conducting such projects. Based on the study's results, we have identified the features of organizing STEAM projects using immersive technologies: expanding the field of creativity with AR and VR, immersion in scientific concepts and conducting experiments through the use of virtual laboratories, visualizing abstract ideas through the use of augmented reality, interacting with technology through mixed reality projects, and teamwork in immersive environments.Conclusions. Immersive technologies in STEAM education have advantages (e.g., gaining practical experience, forming interdisciplinary connections through interdisciplinary learning, cooperation, communication, adaptive environment, and request for creativity) in teaching.
Keywords: immersive technologies; virtual reality; augmented reality; mixed reality; STEAM educational project; general education institution